Developing Nearpod-Based Kentarapod Interactive Media for Improving IPAS Learning Outcomes in Elementary Education - Rohmah, Faidatur; Ratnaningrum, Ika (Edukasi, 2025)
Interactive media plays an important role in digital learning. The primary objectives of this study are to develop the Kentarapod interactive media based on nearpod and to test its feasibility, effectiveness, and practicality. The researchers employed a research and development design, utilizing the ADDIE model, which encompasses analysis, design, development, implementation, and evaluation. This study involved 36 fourth-grade students at SDN Bonjor Rembang. Data were collected through observation, interviews, validation questionnaires, response questionnaires, and pre- and post-tests. Based on the validation results, the product was deemed highly feasible, with a score of 88.33% from subject matter experts and 81.66% from media experts. This interactive media significantly improved the learning outcomes of fourth-grade students at SDN Bonjor Rembang in the subject of IPAS on the topic of my region and its natural resources, with an average pretest-posttest score difference of 42.77 (small group) and 42.6 (large group), and an average N-gain score of 0.7811 and 0.7742 (high category). This media received a very practical evaluation from teachers at 100% and students at 97.7% (small group) and 98.7% (large group). Overall, Kentarapod has proven to be feasible, practical, and effective in improving the learning outcomes of fourth-grade students at SDN Bonjor Rembang.